2012
DOI: 10.1089/rej.2011.1290
|View full text |Cite
|
Sign up to set email alerts
|

How Genes Influence Life Span: The Biodemography of Human Survival

Abstract: Background: In genome-wide association studies (GWAS) of human life span, none of the genetic variants has reached the level of genome-wide statistical significance. The roles of such variants in life span regulation remain unclear. Data and Method: A biodemographic analyses was done of genetic regulation of life span using data on lowsignificance longevity alleles selected in the earlier GWAS of the original Framingham cohort. Results: Age-specific survival curves considered as functions of the number of long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 50 publications
0
19
0
Order By: Relevance
“…Paradoxically, these seemingly sensible strategies pose translational difficulties. The difficulty with studying aging in old humans is that many of them already have age-related diseases (9)(10)(11). Age-related changes to physiology accumulate from early life, affecting organ systems years before disease diagnosis (12)(13)(14)(15).…”
mentioning
confidence: 99%
“…Paradoxically, these seemingly sensible strategies pose translational difficulties. The difficulty with studying aging in old humans is that many of them already have age-related diseases (9)(10)(11). Age-related changes to physiology accumulate from early life, affecting organ systems years before disease diagnosis (12)(13)(14)(15).…”
mentioning
confidence: 99%
“…Some recent studies have shown the promise of this approach by examining how the genetic variants would affect mortality rate and lifespan. Yashin et al (2012), for example, employed the Strehler and Mildvan (SM) theory to explain the shape of mortality trajectories of population subgroups with different numbers of longevity alleles. In this pioneering work, they hypothesized that each longevity allele contributed to an increase in robustness and resistance to stress and thus the number of longevity alleles affected mortality risk through its influence on the initial survival capacity (i.e., vitality) of an individual.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic linkage studies for longevity and several other studies showing an association between human longevity and single nucleotide polymorphisms (SNPs) in a variety of genes in various biological pathways, including heat shock response, mitochondrial functions, immune response, cholesterol metabolism, and others (Singh et al, 2004;Rattan and Singh, 2009;Yashin et al, 2012;Yashin et al, 2013). An analysis of the various functions of the genes associated with aging and longevity shows that these genes cover a wide range of biochemical pathways, such as energy metabolism, kinases, kinase receptors, transcription factors, DNA helicases, membrane glucosidases, GTP-binding protein coupled receptors, chaperones, and cell cycle check point pathways.…”
Section: Genetics Post-genetics and Epigenetics Of Agingmentioning
confidence: 99%